The Morphology of Urban Landscapes: History, Analysis, Design - Gerber, Andri; Iseli, Regula; Kurath, Stefan; Primas, Urs (Dietrich Reimer Verlag, 2021)
The urban morphology investigates settlement and urban forms. These do not change overnight, but in a process that follows certain principles. There is hardly anything more complex and contradictory than a city. Precisely because of this complexity, there is little agreement on definitions and procedural methods. This applies in particular to urban planning, which is not only concerned with analysis, but also with the design and transformation of cities. A variety of different urban morphological approaches exist today. The authors from the areas of research and practice investigate the relevance of the morphological perspective in the field of contemporary urban landscapes. They link historical roots and current approaches and explain the relationship between analysis and design.